"Orbiting the Core": Politics and the Meaning of Dialect in Chinese Linguistics, 1927–1957. (1st September 2016) - Tam, Gina Anne
Abstract : In 1956, the Chinese Communist state launched its official language policy, which included the promulgation of a standard spoken language, called Putonghua. Their justification for this policy and their methods for implementation were guided by intellectual and ideological frameworks that formed during decades preceding the policy's rollout. In particular, Communist language reform was predicated on the conceptualization of Putonghua as a holistic language meant to serve the national body—and of local dialects, called fangyan in Chinese, as dependent on Putonghua for their very definition. This article interrogates the history of this framework. Focusing on dialect surveys from the 1930s, Chinese interpretations of Marxist linguistic theory in the early years of the Communist state, and methods of Putonghua promulgation in the late 1950s, this article reconstructs the epistemological regimes that gave meaning to the concept of independence and autonomy as they related to language in modern China.